NEW BUSINESS MODELS BASED ON DIGITAL TECHNOLOGIES AND THEIR ECONOMIC EFFICIENCY (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
Digital transformation is one of the most important stages of evolution of the modern economy and business world. The rapid development of technology shows that digitalization is not limited to optimizing certain processes, but, on the contrary, reshaping business models as a whole. This transformation does not consist only in the adoption of digital technologies, but also requires a fundamental change in the principles of operation, business processes and customer relations of enterprises. Today, companies are forced to build more flexible and innovative business models in order to gain a competitive advantage in the market. Under the influence of digital technologies, traditional business models are either being rebuilt or completely changed. Thus, thanks to the innovations brought by digitalization, different business models have emerged: joint business models, smart product business models and smart service business models. These models radically change the ways in which enterprises create value, introducing new cooperation formats and customer experiences. At the same time, digital transformation is changing not only business models, but also business processes in the manufacturing and service sectors. The entire value chain, from raw material procurement to sales and customer relations, is being optimized with new digital solutions. These changes ensure closer integration of enterprises with suppliers, manufacturers, customers and other stakeholders, increasing efficiency and competitiveness. This article will comprehensively analyze the new business models brought about by digital transformation and their impact on the development of enterprises. In addition, strategic approaches for the successful adaptation of businesses to the digital era will be presented.Keywords: digital economy, big data, business models, technology